2012
DOI: 10.1111/j.1541-4337.2012.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Treatment Effect on Physicochemical and Nutritional Properties of Fluid Foods During Storage: A Review

Abstract: Consumers demand foods that are easy to consume and that are of high nutritional and sensory quality. Therefore, they appreciate the similarity of minimally processed products to fresh products. In recent years, the food industry has shown increased interest in nonthermal preservation technologies, because they provide products of proven quality and can be an alternative to traditional thermal methods, thus increasing added value. This review examines the effects of high pressure processing (HPP) on the nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(116 citation statements)
references
References 102 publications
6
107
0
3
Order By: Relevance
“…However, among the total answers, 108 interviewed answered that consume these fruits in both, in natura or processed forms. These results corroborate with that observed by other authors (RASEIRA et al, 2010;FACHINELLO et al, 2011;BARBA et al, 2012;GONÇALVES et al, 2016), which cite that there is greater interest in the consumption of these fruits in the in natura form. As these fruits have low to medium shelf life, attention should be paid to harvesting strategies, storage, transportation, packaging and various other security measures, that allow the quality of these fruits to be maintained until they reach the consumer.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, among the total answers, 108 interviewed answered that consume these fruits in both, in natura or processed forms. These results corroborate with that observed by other authors (RASEIRA et al, 2010;FACHINELLO et al, 2011;BARBA et al, 2012;GONÇALVES et al, 2016), which cite that there is greater interest in the consumption of these fruits in the in natura form. As these fruits have low to medium shelf life, attention should be paid to harvesting strategies, storage, transportation, packaging and various other security measures, that allow the quality of these fruits to be maintained until they reach the consumer.…”
Section: Resultssupporting
confidence: 93%
“…These traits are appealing to consumers, because increase the organoleptic attributes of the fruits and are thus preferred by consumers (CAMPBELL et al, 2004;BARBA et al, 2012;GONÇALVES et al, 2016;MONTI et al, 2016;SILVA et al, 2016;DROGOUDI et al, 2017;TECHAKANON and BARRETT, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore high pressure processing is recommended to produce stable nutrient rich and better quality juice. Various studies showed that, sensorial properties of pressure treated fruit juice samples are more or less comparable with control samples (Daoudi et al, 2002;Matser et al, 2004;Barba et al, 2012) due to minimal or limited effect of pressure on various chemical bonds. In terms of safety point of view, by choosing appropriate pressure treatment conditions (like higher pressure shorter time or vise versa), it is possible to kill pathogenic and spoilage vegetative cells to get shelf stable fruit juices stored at refrigerated temperature (Matser et al, 2004;Black et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The increase was more pronounced comparing with pasteurized samples. The total colour difference (ΔE) indicates the magnitude of colour difference between processed and unprocessed fluid foods (Barba et al, 2012). The calculated values for total colour change in milk samples are provided in Table 2.…”
Section: Instrumental Evaluation Of Colourmentioning
confidence: 99%